2009
DOI: 10.1002/jmr.968
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of human group IIA phospholipase A2 inactivation by bolinaquinone

Abstract: The molecular basis of the human group IIA secretory phospholipase A(2) inactivation by bolinaquinone (BLQ), a hydroxyquinone marine terpenoid, has been investigated for the comprehension of its relevant antiinflammatory properties, through the combination of spectroscopic techniques, biosensors analysis, mass spectrometry (MS) and molecular docking. Indeed, sPLA(2)s are well known to be implicated in the pathogenesis of inflammation such as rheumatoid arthritis, septic shock, psoriasis and asthma. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Such data were in agreement with the biological assays, where BLQ inhibits GIIA sPLA 2 and bee venom GIII sPLA 2 with IC 50 values of 0.2 and 0.1 GM, respectively [46,72,77]. It was suggested that the comprehension of the mechanism of the enzyme inhibition would allow a rational design of simplified analogues of natural products as novel lead compounds with anti-inflammatory properties.…”
Section: Marine Natural Productssupporting
confidence: 81%
See 1 more Smart Citation
“…Such data were in agreement with the biological assays, where BLQ inhibits GIIA sPLA 2 and bee venom GIII sPLA 2 with IC 50 values of 0.2 and 0.1 GM, respectively [46,72,77]. It was suggested that the comprehension of the mechanism of the enzyme inhibition would allow a rational design of simplified analogues of natural products as novel lead compounds with anti-inflammatory properties.…”
Section: Marine Natural Productssupporting
confidence: 81%
“…7) is a sesquiterpene metabolite isolated from the marine Dysidea sponge. This metabolite inhibits human GIIA sPLA 2 with IC 50 value of 0.245 DM [46]. Based on docking calculations, it was found that BLQ participates in hydrophobic contacts with the hydrophobic region of GIIA sPLA 2 active site formed by the residues Leu2, Phe5, His6, Ala17, Ala18, Tyr21, Gly22, Gly25, Cys28, Gly29, Cys44, Phe98.…”
Section: Bolinaquinone (Blq)mentioning
confidence: 99%
“…As already carried out in our previous studies on sPLA 2 , [13][14][15][16][17][21][22][23] we started with the analysis of sPLA 2 potential covalent modification by CLD A through liquid chromatography-nano-ESI MS (LC-nano-ESI-MS). Time-course analysis of the CLD A and sPLA 2 -IIA reaction mixture was performed, and the chromatograms revealed the presence of the unmodified sPLA 2 -IIA (M W 13 860.05(AE0.45) Da) and of a species corresponding to a 1:1 sPLA 2 -IIA-CLD A covalent adduct with a mass increment of approximately 384 Da ( Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…As we wanted to determine the role of the noncovalent interactions in sPLA 2 -IIA inactivation by CLD A, we resorted to the use of p-nitrophenacyl bromide (pNBr, M W = 244 Da), a well-known specific ligand of the catalytic His resi- [17,[22][23][24] Indeed, comparative pNBr modification experiments in the presence and absence of a given inhibitor provides valuable clues about the inhibition mechanism (if competitive or not). We incubated sPLA 2 -IIA in the presence of pNBr and detected by LC-MS a significant amount of sPLA 2 -IIA covalently modified by this agent (Figure 2, back).…”
Section: Identification Of Spla 2 -Iia Modification Sitementioning
confidence: 99%
See 1 more Smart Citation